Blue whales (Balaenoptera musculus) optimize foraging efficiency by balancing oxygen use and energy gain as a function of prey density - Hazen, Elliott Lee (Sci Adv, 2015)
Terrestrial predators can modulate the energy used for prey capture to maximize efficiency, but diving animals face the conflicting metabolic demands of energy intake and the minimization of oxygen depletion during a breath hold. It is thought that diving predators optimize their foraging success when oxygen use and energy gain act as competing currencies, but this hypothesis has not been rigorously tested because it has been difficult to measure the quality of prey that is targeted by free-ranging animals. We used high-resolution multisensor digital tags attached to foraging blue whales (Balaenoptera musculus) with concurrent acoustic prey measurements to quantify foraging performance across depth and prey density gradients. We parameterized two competing physiological models to estimate energy gain and expenditure based on foraging decisions. Our analyses show that at low prey densities, blue whale feeding rates and energy intake were low to minimize oxygen use, but at higher prey densities feeding frequency increased to maximize energy intake. Contrary to previous paradigms, we demonstrate that blue whales are not indiscriminate grazers but instead switch foraging strategies in response to variation in prey density and depth to maximize energetic efficiency.